PRICING IMPROVEMENT OF WATER SUPPLY AND PLUMBING SERVICES AS A PUBLIC-PRIVATE PARTNERSHIPS' STIMULUS - E. Moroz (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The necessity of the transition to the tariffs' formation in the water supply and plumbing sphere on the stimulating regulation' principles are substantiated in the article. The feasibility of public-private partnerships in the water supply and plumbing sphere of Ukraine are analyzed and introduction' and development' preconditions of such cooperation are demonstrated.